ARTICLE REVIEW : TINJAUAN DAMPAK PENERAPAN TELEFARMASI TERHADAP PENINGKATAN PELAYANAN KESEHATAN PASIEN DI APOTEK - Rambe, Sahrum; Suryani, Suryani (Jurnal Buana Farma, 2025)
The growing demand for efficient and accessible healthcare services especially in the context of geographical challenges and the post-pandemic environment has driven the development of innovations such as telepharmacy. Telepharmacy, as a subset of telemedicine, expands access to pharmaceutical services through communication technology and represents a significant breakthrough in healthcare delivery by supporting pharmacists in providing pharmaceutical care information. Although the adoption of telepharmacy in Indonesia is still progressing, this article aims to review its impact on improving the quality of healthcare services, particularly within the Indonesian context. Relevant literature on telepharmacy implementation in Indonesia was retrieved from Google Scholar, PubMed, and other academic platforms, focusing on publications from 2015 to 2025. The purpose of evaluating these articles was to ensure that their content met established standards. Nine articles discussing the use of telepharmacy which has been increasingly adopted in healthcare settings, especially in community pharmacies were selected for this review. Findings from the literature indicate that telepharmacy can enhance healthcare quality by reducing costs, improving the efficiency of pharmaceutical services, and decreasing prescription errors. As an alternative approach to expanding service coverage and reaching rural areas, telepharmacy has also been widely adopted in pharmacies, enabling pharmacists to contribute more effectively to improving medication use.